2013
DOI: 10.3109/00016489.2012.746470
|View full text |Cite
|
Sign up to set email alerts
|

Tenotomy of the stapedius and tensor tympani muscles reduces subjective dizziness handicap in definite Meniere's disease

Abstract: A statistically significant reduction of 48 DHI points, from a median preoperative DHI = 52 to DHI = 4 postoperatively, was noted (p < 0. 001). In all, 40/42 patients reported a reduction of dizziness handicap, while in 33/42 the difference was > 12 points. A statistically significant reduction of DHI scores was noted (A = 60, B = 34, C = 33) in all subgroups. It was also noted that the higher the preoperative DHI score, the greater the subjective success of the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
6
0
4
Order By: Relevance
“…Тенотомия стременной мышцы и мышцы, напрягающей барабанную перепонку, исследована рядом авторов как способ лечения болезни Меньера, хотя они отмечают, что эффективность этого метода достоверно не доказана [14][15][16][17][18]. Другие авторы пишут о пересечении мышцы, напрягающей барабанную перепонку, включая доступ к переднему эпитимпануму и выделению молоточка, при тимпанопластике и оссикулопластике [13,18].…”
Section: Mиоклонус мышц среднего ухаunclassified
“…Тенотомия стременной мышцы и мышцы, напрягающей барабанную перепонку, исследована рядом авторов как способ лечения болезни Меньера, хотя они отмечают, что эффективность этого метода достоверно не доказана [14][15][16][17][18]. Другие авторы пишут о пересечении мышцы, напрягающей барабанную перепонку, включая доступ к переднему эпитимпануму и выделению молоточка, при тимпанопластике и оссикулопластике [13,18].…”
Section: Mиоклонус мышц среднего ухаunclassified
“…In a subsequent investigation of 42 patients with a follow-up time of up to 9 years, Loader et al reported a significant reduction of the dizziness handicap inventory (DHI), a questionnaire on the subjective self-assessment of the impairment by vertigo complaints. It could also be shown that the therapeutic success was higher, the more severe the preoperative impairment was estimated [ 54 ].…”
Section: Hydropic Inner Ear Diseases – Menière’s Disease and Menièrmentioning
confidence: 99%
“…Loader et al berichten in einer Folgeuntersuchung über eine Reduktion der Dizziness Handicap Inventory (DHI), eines Erfassungsbogens zur subjektiven Selbsteinschätzung der Beeinträchtigung durch die Schwindelbeschwerden, in einer Studie an 42 Patienten mit einem Nachbeobachtungszeitraum von bis zu 9 Jahren. Hier zeigte sich, dass der therapeutische Erfolg umso besser ausfiel, je höher die präoperative Beeinträchtigung eingeschätzt wurde [54].…”
Section: Tenotomie Der Sehnen Des M Stapedius Und Des M Tensor Tympaniunclassified